Control of the Surface Disorder by Ion‐Exchange to Achieve High Open‐Circuit Voltage in HC(NH2)2PbI3 Perovskite Solar Cell. Issue 12 (15th October 2021) - Chen, Siqi; Wang, Jin; Ran, Guangliu; Pan, Qingyan; Liu, Le; Zhao, Chengjie; Tang, Jin; Zhao, Min; Zhang, Wenkai; Zhao, Yingjie; Jiu, Tonggang
Abstract: The ionic nature of organic trihalide perovskite leads to structural irregularity and energy disorder at the perovskite surface, which seriously affects the photovoltaic performance of perovskite solar cells. Here, the origin of the perovskite surface disorder is analyzed, and a facial ion‐exchange strategy is designed to regulate the surface chemical environment. By the reconstruction of terminal irregular Pb–I bonds and random cations, the repaired surface is characteristic of the reduced band tail states, consequent to the suppression of the uplift of quasi‐Fermi level splitting and photocarrier scattering. The optimized device gets a high open‐circuit voltage and operational stability. These findings fully elaborate the underlying mechanism concerning perovskite surface problem, giving guidance on tailoring the energy disorder. Abstract : A facile ion‐exchange strategy is applied to stabilize the surface outermost structure and the origination of FAPbI3 perovskite surface disorder is unveiled. The replacement between metastable FA cation with stable acetamidine hydroiodide (AMH) cation reconstructs an energetic favorable surface, which suppresses the multirecombination paths, delivering a high open‐circuit voltage value for the narrow bandgap FAPbI3 perovskite solar cell.